2001
DOI: 10.1046/j.1365-2699.2001.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of the Antilles based on a parsimony analysis of orchid distributions

Abstract: Aim We obtain biogeographical patterns based on the distributions of shared orchid species of the Caribbean. These patterns are used to define biogeographical zones. We then analyse the concordance between the distributional patterns with ecological and physical features of the islands. Location We use orchid species recorded on 49 islands of the Greater, Lesser, and southern Antilles, and the Bahamas. Three continental areas are included: Florida (North America), the Yucatan (Central America), and the Guianas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 46 publications
1
71
0
6
Order By: Relevance
“…, 1994, Hietz & Hietz‐Seifert, 1995). Trejo‐Torres & Ackermann (2001) have shown that the overlap in the Orchid inventories of distanced Caribbean islands was high, when the physiographic and ecological conditions allowed the species presence. In contrast, even neighbouring islands had a small floristic overlap if their physiognomy was different.…”
Section: Ecological Dissimilaritymentioning
confidence: 99%
“…, 1994, Hietz & Hietz‐Seifert, 1995). Trejo‐Torres & Ackermann (2001) have shown that the overlap in the Orchid inventories of distanced Caribbean islands was high, when the physiographic and ecological conditions allowed the species presence. In contrast, even neighbouring islands had a small floristic overlap if their physiognomy was different.…”
Section: Ecological Dissimilaritymentioning
confidence: 99%
“…It has been shown that ecological traits determining the vagility potential of species can affect their distributions (e.g., Doyen and Tschinkel 1974;Lomolino 1983;Shine 1987;Trejo-Torres and Ackerman 2001). Here I use a scenario of two islands to describe possible modes of evolution of geographic ranges and discuss the central role of vagility.…”
Section: Introductionmentioning
confidence: 99%
“…Muitas vezes, as OGUs são quadrículas (Morrone 1994). O mesmo foi utilizado em várias espécies animais e vegetais (Posadas & Miranda-Esquivel 1999, Trejjo-Torres & Ackerman 2001, Garcia-Barros et al 2002, Morrone & Escalante 2002, Rovito et al 2004. Craw (1988) sugeriu utilizar áreas de endemismo predeterminadas e Silva & Oren (1996) escolheram áreas interfluviais.…”
Section: Methodsunclassified